Estrategias de comprensión lectora en el proceso formativo de educación básica media - Guacialpud Changoluisa, Martha Narcisa (2017)
Reading comprehension is one of the problems that cause controversy in teachers of all levels of education; there is a lot of concern about how to get students to understand what they read. That is why this research project aims at determining the shortcomings that affect the formative process of reading comprehension in the students of fifth, sixth and seventh grade at José Mejia Lequerica Educative Unit. This is a bibliographic research, by using quantitative methods and its scope is descriptive. Surveys were applied to the teachers and students of the aforementioned institution in order to know their criteria regarding the teaching and learning process of reading comprehension. The data found indicate that teachers use traditional methodologies such as summaries and mechanical reading tasks. The reading process that integrates pre-reading, reading and post-reading is not developed. In addition, it was determined that there is a lack of interest for reading in students due to teachers does not use innovative reading comprehension strategies. These results suggest that more attention should be given to the development of reading in the classroom as this allows fostering learning. Teaching training projects must be developed to strengthen the development of reading comprehension through an adequate process that integrates innovative strategies, which benefits students’ integral education and the educational community in general.